2016
DOI: 10.1007/s10995-016-2015-z
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Protective Effect of Exclusive Breastfeeding on Child Overweight and Obesity by Mother’s Race

Abstract: Objectives To examine the relationship between infant feeding and risk of child overweight and obesity across race and ethnicity in a diverse community-based cohort. Methods 2172 mother baby dyads were drawn from a prospective cohort constructed using data from electronic medical records linked to birth records. The primary exposure was exclusive breastfeeding at 2 months of age; outcome was BMI Z-score and BMI ≥ 85th percentile (overweight and obese) at 4 years of age. Regression models were adjusted for conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 59 publications
(50 reference statements)
1
17
0
6
Order By: Relevance
“…We observed that, compared with exclusive breastfeeding for less than 3 months, exclusive breastfeeding for 6 months or longer was associated (after adjustment for confounders) with lower BMI and lower risk of overweight at age 5–6 years in risk groups of medium education, Dutch ethnicity (indicated by logistic regression and adjusted linear regression models) and normal BMI. Similar to our study, studies in the USA and Sweden stratified their analyses by maternal ethnicity and concluded that the protective effect of breastfeeding (any duration, non‐exclusive) on overweight/obesity or BMI development was limited to children of White mothers and not observed in Blacks, Hispanics or non‐Swedish immigrants . One of these studies also examined a low‐income population in which the effect was limited only to White children who were breastfed at least for 4 months and whose mothers did not smoke .…”
Section: Discussionsupporting
confidence: 81%
“…We observed that, compared with exclusive breastfeeding for less than 3 months, exclusive breastfeeding for 6 months or longer was associated (after adjustment for confounders) with lower BMI and lower risk of overweight at age 5–6 years in risk groups of medium education, Dutch ethnicity (indicated by logistic regression and adjusted linear regression models) and normal BMI. Similar to our study, studies in the USA and Sweden stratified their analyses by maternal ethnicity and concluded that the protective effect of breastfeeding (any duration, non‐exclusive) on overweight/obesity or BMI development was limited to children of White mothers and not observed in Blacks, Hispanics or non‐Swedish immigrants . One of these studies also examined a low‐income population in which the effect was limited only to White children who were breastfed at least for 4 months and whose mothers did not smoke .…”
Section: Discussionsupporting
confidence: 81%
“…In addition, there are a high number of maternal and infant factors that influence the levels of bioactive compounds in human milk and their functions in the infant gut. These factors pinpoint the difficulty in relating unequivocally the variation of one compound to a specific infant outcome ( 86 , 92 ). From a methodological point of view, care must be taken to compare some of the obtained results because of the strong association of some compounds to the milk fat fraction, which was discarded during sample preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Children with obese mothers seem to be at higher risk to become obese themselves [ 35 ]. The protective effect of breastfeeding against early childhood obesity may differ with race and ethnicity [ 36 ].…”
Section: Discussionmentioning
confidence: 99%